Evaluating complementary and alternative medicine interventions: in search of appropriate patient-centered outcome measures - Mallory Devon; Dryden Trish; Vanderheyden Laura C; Verhoef Marja J; Ware Mark A (BMC, 2006)
Abstract Background Central to the development of a sound evidence base for Complementary and Alternative Medicine (CAM) interventions is the need for valid, reliable and relevant outcome measures to assess whether the interventions work. We assessed the specific needs for a database that would cover a wide range of outcomes measures for CAM research and considered a framework for such a database. Methods The study was a survey of CAM researchers, practitioners and students. An online questionnaire was emailed to the members of the Canadian Interdisciplinary Network for CAM Research (IN-CAM) and the CAM Education and Research Network of Alberta (CAMera). The majority of survey questions were open-ended and asked about outcome measures currently used, outcome measures' assessment criteria, sources of information, perceived barriers to finding outcome measures and outcome domains of importance. Descriptive quantitative analysis and qualitative content analysis were used. Results One hundred and sixty-four completed surveys were received. Of these, 62 respondents reported using outcome measures in their CAM research and identified 92 different specific outcomes. The most important barriers were the fact that, for many health concepts, outcome measures do not yet exist, as well as issues related to accessibility of instruments. Important outcome domains identified included physical, psychological, social, spiritual, quality of life and holistic measures. Participants also mentioned the importance of individualized measures that assess unique patient-centered outcomes for each research participant, and measures to assess the context of healing and the process of healing. Conclusion We have developed a preliminary framework that includes all components of health-related outcomes. The framework provides a foundation for a larger, comprehensive collection of CAM outcomes. It fits very well in a whole systems perspective, which requires an expanded set of outcome measures, such as individualized and holistic measures, with attention to issues of process and context.